National strategy for adaptation to climate change in the agricultural sector in Honduras (2015-2025) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
This strategy issued by the secretary of agriculture (SAG), with the support of CCAFS science (OICR 3148), defines strategic lines for climate change adaptation in the Honduran agricultural sector.